2002
DOI: 10.1074/jbc.m110355200
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-sensitive Lipase Deficiency in Mice Causes Diglyceride Accumulation in Adipose Tissue, Muscle, and Testis

Abstract: Hormone-sensitive lipase (HSL) is expressed predominantly in white and brown adipose tissue where it is believed to play a crucial role in the lipolysis of stored triglycerides (TG), thereby providing the body with energy substrate in the form of free fatty acids (FFA). From in vitro assays, HSL is known to hydrolyze TG, diglycerides (DG), cholesteryl esters, and retinyl esters. In the current study we have generated HSL knock-out mice and demonstrate three lines of evidence that HSL is instrumental in the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
538
6
7

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(577 citation statements)
references
References 58 publications
26
538
6
7
Order By: Relevance
“…The intracellular rates of lipolysis by ATGL, HSL, and MGL were estimated from the difference between AVDs of glycerol and TG such that ~15% of the produced FA are re-utilized inside adipose tissue (Frayn et al, 1994;Coppack et al, 1990). Finally, fluxes through individual lipase reaction were estimated based on the 10-fold higher activity that HSL has for DG than for TG and MG (Shen et al, 1998;Haemmerle et al, 2002). Thus, the flux rate for DG breakdown by HSL was calculated first and then those for TG and MG breakdown by HSL.…”
Section: Model Specifications and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular rates of lipolysis by ATGL, HSL, and MGL were estimated from the difference between AVDs of glycerol and TG such that ~15% of the produced FA are re-utilized inside adipose tissue (Frayn et al, 1994;Coppack et al, 1990). Finally, fluxes through individual lipase reaction were estimated based on the 10-fold higher activity that HSL has for DG than for TG and MG (Shen et al, 1998;Haemmerle et al, 2002). Thus, the flux rate for DG breakdown by HSL was calculated first and then those for TG and MG breakdown by HSL.…”
Section: Model Specifications and Assumptionsmentioning
confidence: 99%
“…However, recently, it has been shown that the HSL deficient mice retain the basal lipolysis rate and respond to the beta-adrenergic stimulation, although the response was quantitatively less than in the wild type (Okazaki et al, 2002;Zechner et al, 2005;Haemmerle et al, 2002). The accumulation of diglycerides (DG) in the adipose tissue of HSL knockout mice suggests that HSL is the rate limiting enzyme for the hydrolysis of DG and not TG (Haemmerle et al, 2002). Adipose TG lipase (ATGL) has been suggested to be the key enzyme involved in TG hydrolysis in the adipose tissue (Schweiger et al, 2006;Haemmerle et al, 2006;Zimmermann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lipolytic hormone-stimulated, protein kinase A-mediated phosphorylation of both HSL and perilipin results in hydrolysis of triglyceride into NEFAs and monoglyceride, which is further converted to NEFA and glycerol by monoglyceride lipase (MGL) [8]. Recent studies showing that adipocytes from HSL knockout mice retain a marked basal and adrenergically stimulated lipolysis and accumulate diglycerides after stimulation of lipolysis demonstrated that HSL is not the sole lipase involved in triglyceride catabolism [9][10][11]. Three independent groups have discovered a protein-alternatively termed adipose triglyceride lipase (ATGL) [12], desnutrin [13] or calcium-independent phospholipase A 2 /lipase ζ (iPLA 2 ζ) [14]-that fulfils all the predicted characteristics of this new lipase: a preference for the hydrolysis of the first triglyceride ester bond, drastically reduced lipolysis following antibody or antisense ATGL inhibition, and enhanced basal and isoproterenol-stimulated lipolysis following ATGL overexpression [15].…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme possesses tri-and diglyceride hydrolase activities and is regulated by the major lipolysis-regulating hormones, which in man are insulin, catecholamines and natriuretic peptides [3]. However, HSL knock-out mice have residual lipolytic activity [4,5], which may be attributed to an additional lipase with high affinity for triglycerides [6,7]. Accordingly, a novel adipocyte-specific lipase termed adipose triglyceride lipase (ATGL, now known as patatin-like phospholipase domain containing 2 [PNPLA2]), the product of Pnpla2, and alternatively designated iPLA 2 ζ or desnutrin, was recently identified using different strategies [8][9][10].…”
Section: Introductionmentioning
confidence: 99%